Microplastics in Our Environment: Assessing Sources, Fate, and Health Impacts - Pandit, Jyotsana; Sharma, Anish (Journal of Food Health and Bioenvironmental Science, 2025)
Microplastic pollution, a pervasive environmental issue, has garnered significant global attention due to its adverse impacts on human health and ecosystems. This review paper examines the origins, environmental behaviour, and consequences of microplastics, which are plastic particles less than 5 mm in size. The ubiquitous presence of microplastics in aquatic, terrestrial, and atmospheric environments poses significant hazards to human health and biodiversity. Microplastics infiltrate the food chain by being ingested by marine organisms, accumulating in higher trophic levels, and ultimately becoming available to humans. This review focuses on the potential health impacts, environmental behavior, and numerous sources of microplastics. Additionally, it underscores existing mitigation initiatives, including the circular economy, recycling, and waste management, while advocating for more stringent regulations and public education to reduce plastic contamination. Safeguarding public health and ecosystems necessitates sustainable consumption practices, technological innovation, and global collaboration to address the microplastic crisis.